2016
DOI: 10.1002/ijch.201600002
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Molecular Configuration in Twisted Crystal Form

Abstract: Structural chemistry began with Louis Pasteur, who first saw the configuration of molecules manifest in the shapes of crystals. Here is reviewed forgotten, century‐old efforts to make molecular configuration vivid in polycrystalline ensembles. Resorcinol, and a variety of other simple molecular crystals, when grown from the melt in the presence of resolved chiral additives, such as tartaric acids, form spectacular bull's‐eye patterns evident in the petrographic microscope. Concentric, rhythmic optical bands in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A large proportion (up to one-third) of molecular crystals can be made to twist as they grow. 38,[110][111][112][113] In some families of crystals, such as binary charge transfer complexes, the proportion can be greater than one-half. 114 This group includes many common materials that have been studied for decades or more.…”
Section: Ubiquitymentioning
confidence: 99%
See 2 more Smart Citations
“…A large proportion (up to one-third) of molecular crystals can be made to twist as they grow. 38,[110][111][112][113] In some families of crystals, such as binary charge transfer complexes, the proportion can be greater than one-half. 114 This group includes many common materials that have been studied for decades or more.…”
Section: Ubiquitymentioning
confidence: 99%
“…Many twisted crystals display their nonclassical morphologies in the absence of impurities (in evidence), while in other cases, additives appear to be crucial to the process of twisted crystal growth. Impurities [110] to [210] and then to [310] with respect to the incident electron beam. Adapted with permission from ref.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiroptics remained at the center of French physical optics 72 since the work of Arago, 73 Biot, Fresnel, and Pasteur (1822-1895) 74 in the first part of the 19th century. Arago first observed the consequences of optical rotatory dispersion in quartz, Biot first observed that solutions of some organic molecules can rotate the plane of polarization, and Pasteur established the first correlation between macroscopic chirality in the shapes of crystals and microscopic chirality in the action of molecules liberated from dissymmetric crystals on the azimuth of linearly polarized light.…”
Section: àBzþamentioning
confidence: 99%
“…The spherulitic crystal growth morphology becomes more complex if crystallites spontaneously twist as they grow. Such so-called banded spherulites display oscillating linear birefringence (LB) as a consequence of continuous changes in crystallite orientation and refractivity. , In general, up to one-third of molecular crystals can be made to twist as they grow from the melt. In some families of crystals, such as binary charge transfer complexes (CTCs), the proportion can be greater than one-half . Due to the anisotropy of crystal cross section shape and branching frequency, twisting substantially complicates fiber organization in spherulites.…”
Section: Introductionmentioning
confidence: 99%